Health Screening and Updated Blood Pressure Guidelines and Their Application for the Certified Personal Trainer. Issue 6 (December 2021) - Young, Jeff
Abstract : ABSTRACT: Certified National Strength and Conditioning Association personal trainers are "health/fitness professionals who, using an individualized approach, assess, motivate, educate, and train clients regarding their health and fitness needs. They design safe and effective exercise programs, provide the guidance to help clients achieve their personal health/fitness goals, and respond appropriately in emergency situations. Recognizing their area of expertise, personal trainers refer clients to other health care professionals when appropriate." The design of safe and effective exercise programs includes the need to stay current with published research and changes to relevant exercise guidelines. The purpose of this article is to provide a brief overview of recent changes to the exercise preparticipation health screen, application of the physical activity readiness questionnaire for everyone (PAR-Q+), updated blood pressure guidelines, and recommendations for program design given these changes. Abstract : Supplemental Digital Content is Available in the Text.